2017
DOI: 10.3928/24748307-20170711-01
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Access Choice: Impact of Health Literacy

Abstract: Background: Hemodialysis patients need to make decisions about vascular access and diet that they may not fully understand. In this study, we hypothesized that patients with low health literacy are likely to choose a central venous catheter (CVC) and have higher serum potassium (K), serum phosphate (P), and inter-dialysis weight gains (IDWG). Objective: Primarily, the study sought to describe the health literacy of patients treated with hemodialysis in a Canadian tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…We found that patients with greater ability to engage with healthcare providers, those with better ability to navigate the healthcare system, those more able to find good health information, and those who understand it well enough to know what to do are more likely to have AVF as their VA. Cavanaugh et al [23] brought similar findings, whereby dialyzed patients with limited HL were more likely to have CVC. Mazarova et al [12] focused on functional HL in dialyzed patients and their choice of the type of VA, and they found that patients with low HL were more likely to prefer CVC. They concluded that this is due to a lack of education and information for patients from healthcare providers needed for informed decision-making about their VA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that patients with greater ability to engage with healthcare providers, those with better ability to navigate the healthcare system, those more able to find good health information, and those who understand it well enough to know what to do are more likely to have AVF as their VA. Cavanaugh et al [23] brought similar findings, whereby dialyzed patients with limited HL were more likely to have CVC. Mazarova et al [12] focused on functional HL in dialyzed patients and their choice of the type of VA, and they found that patients with low HL were more likely to prefer CVC. They concluded that this is due to a lack of education and information for patients from healthcare providers needed for informed decision-making about their VA.…”
Section: Discussionmentioning
confidence: 99%
“…A well-functioning VA is essential for effective hemodialysis treatment, but the selection of the VA type requires taking into consideration many factors that affect the possible access failure, such as the patient's demographic factors, the patient's adherence to fistula care, and cooperation between healthcare professionals and the patient [2,5]. Several modifiable factors are associated with the selected type of VA, such as the patients' preference [10,11] and health literacy (HL) [12].…”
Section: Introductionmentioning
confidence: 99%
“…We also did not verify that patients were truly making informed choices about the potential risks versus benefits of the two cannulation techniques. Low health literacy has been associated with hemodialysis access choice, but may not apply to patients on home hemodialysis or cannulation technique (31). Alternatively, there may also be health care provider preference for training patients to do buttonhole instead of stepladder cannulation (15).…”
Section: Discussionmentioning
confidence: 99%
“…In HD treatment, there are 3 possible options for vascular access: arteriovenous fistula (AVF), arteriovenous graft (AVG) and HD central venous catheter (CVC) 4 (see, Figure 1). Although both AVFs and AVGs are preferred over CVCs as permanent hemodialysis vascular access devices for HD patients, CVCs can still be the initial choice although they cause higher risk of mortality, fatal infection, and cardiovascular events when used permanently 5 . In the United States, about 70 to 80% of patients undergoing HD therapy use CVC initially 6 .…”
Section: Introductionmentioning
confidence: 99%